A cross sectional study to assess anemia & its determinants among pregnant women in a rural area of Maharashtra - Puri, Dipali C; Rasal, Milind M; Giri, Purushottam A (Indian Journal of Community Health, 2024)
Background: In India, anaemia prevalence is more than 40% so it is a severe public health problem. National Family Health Survey V indicates that prevalence of anaemia in pregnant women in Maharashtra’s rural areas is 46.5%. As the pregnant women have high prevalence of anaemia, it highlights the need to conduct research to find out the determinants and its preventive measures. Aim: To determine prevalence of anaemia and to assess its determinants amongst pregnant women in a rural area Methods: Three eighty-four pregnant women in a rural area of Thane district were selected for a community based descriptive cross-sectional study. Association between anaemia and variables in the study was established using Pearson‘s Chi- square test. For studying association between anaemia as dependent variable and various determinants as independent variables, binary logistic regression analysis was used. Results: Prevalence of anaemia was found to be 62.5%. 29.2% participants were mildly anaemic, 33.0% were moderately anaemic, 0.3% were severely anaemic and 37.5% were non-anaemic. Occurrence of anaemia was significantly associated with age, religion, gravida status, trimester, gestational age at first ANC visit, no consumption of IFA tablets, no consumption of dark green leafy vegetables and dietary habits. Conclusions: High prevalence of anaemia amongst pregnant women reflects poor utilization of health care services, lack of awareness about adequate dietary patterns and poor nutritional status. Anaemia is still a severe public health issue amongst pregnant women of rural areas.